2002
DOI: 10.1111/j.1477-9552.2002.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical, Allocative, Cost and Scale Efficiencies in Bangladesh Rice Cultivation: A Non‐parametric Approach

Abstract: Applying programming techniques to detailed data for 406 rice farms in 21 villages, for 1997, produces inefficiency measures, which differ substantially from the results of simple yield and unit cost measures. For the Boro (dry) season, mean technical efficiency was 69.4 per cent, allocative efficiency was 81.3 per cent, cost efficiency was 56.2 per cent and scale efficiency 94.9 per cent. The Aman (wet) season results are similar, but a few points lower. Allocative inefficiency is due to overuse of labour, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
205
8
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(259 citation statements)
references
References 19 publications
36
205
8
10
Order By: Relevance
“…Other factors like experience, family size and extension service were insignificant. Alam (2011) and Coelli et al (2002) also found the insignificant relation between experience and efficiency.…”
Section: Factors Affecting Efficiency Of Tomato Farmersmentioning
confidence: 99%
“…Other factors like experience, family size and extension service were insignificant. Alam (2011) and Coelli et al (2002) also found the insignificant relation between experience and efficiency.…”
Section: Factors Affecting Efficiency Of Tomato Farmersmentioning
confidence: 99%
“…As stated by Coelli et al (2002), cost efficiency and allocative efficiency can be estimated by DEA. 5 The cost efficiency evaluates how much total input costs can be decreased without decreasing output.…”
Section: Cost and Allocative Efficiency Of Input Resource Usementioning
confidence: 99%
“…Tauer and Hanchar's (1995) Monte Carlo simulations suggest that measures of efficiency are more sensitive to changes in the number of products and inputs than to changes in the number of observations. Finally, Coelli et al (2002) showed that many firms could spuriously appear on the DEA frontier when the sample is small and there are many inputs.…”
Section: Issues In Efficiency Measurement Techniquesmentioning
confidence: 99%
“…Finally, the SPF approach is suited only for single-output technologies. A multi-output case can only be studied if the various outputs can be aggregated into a single aggregate output (Coelli et al, 2002).…”
Section: Issues In Efficiency Measurement Techniquesmentioning
confidence: 99%